Enhancing Multimodal Route Optimization in Maritime Transport: Integrating Real-Time Data and Professionalism - Sijabat, Panderaja Soritua; Retno Sawitri Wulandari; Wardoyo Dwi Kurniawan; Meriyanti Agustinawati; Marudut Bernadtua Simanjuntak (LPPM POLITEKNIK LP3I BANDUNG, 2024)
This research investigates methods to enhance multimodal route optimization in the maritime sector through the integration of real-time traffic data and professionalism standards. Conducted by researchers and lecturers at the Maritime Institute, the study involves 100 cadets predominantly studying multimodal transportation, logistics, and port management. The research utilises qualitative methods to explore cadets' perspectives on route optimization and professionalism in the industry. Findings reveal a recognition of the significance of real-time traffic data for informed routing decisions, along with an emphasis on compliance with international standards, training, and ethical considerations. Furthermore, cadets perceive machine learning algorithms as effective tools to address the complexities of route optimization. These insights contribute to advancing knowledge in transportation management and education, highlighting the importance of integrating real-time data and professionalism in enhancing route optimization practices.